2011
DOI: 10.1111/j.1365-2214.2010.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular morbidity in hearing impaired schoolchildren

Abstract: Hearing impaired children are at an increased risk of having ocular morbidity. Hence, periodic eye examinations are important in deaf children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…This study showed a slightly higher incidence (50%) of ocular pathologies in congenitally deaf patients. In the same manner, refractive disorders were the leading pathology, with a higher incidence of 44.9% (35 cases), compared to the 16%-42.7% found across previously published studies (4,7,(9)(10)(11)(16)(17)(18)(19)(20). Since our study group was composed of adult individuals, it was easy to detect even a small degree of refractive problems like myopia, which may increase during the adolescent years.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This study showed a slightly higher incidence (50%) of ocular pathologies in congenitally deaf patients. In the same manner, refractive disorders were the leading pathology, with a higher incidence of 44.9% (35 cases), compared to the 16%-42.7% found across previously published studies (4,7,(9)(10)(11)(16)(17)(18)(19)(20). Since our study group was composed of adult individuals, it was easy to detect even a small degree of refractive problems like myopia, which may increase during the adolescent years.…”
Section: Discussionsupporting
confidence: 58%
“…Published studies have shown that the rate of ophthalmologic pathologies in SNHL cases ranges between 31% and 48% (4,(7)(8)(9)(10)(11)(16)(17)(18)(19). A summary of frequency of ophthalmic pathologies from different studies is listed in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show that the prevalence of ocular morbidity is more common in hearing impaired children than the normal school children of the same age group [18][19][20] . Similarly, the refractive error is more common in the hearing impaired children than the normal school children [18][19][20] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the refractive error is more common in the hearing impaired children than the normal school children [18][19][20] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Various methodologies and classification criteria have been used in the assessment of vision/visual acuity (Table 3). Bist et al (2011), for example, assessed vision and visual acuity with a Snellen tumbling 'E' test chart, which do not require literacy. Whilst most research has used traditional Snellen charts at 6 m, there has been little use of LogMAR assessment despite it being acknowledged as a superior measurement (Lovie-Kitchin 2008).…”
Section: Visual Defectsrefractive and Binocular Vision Abnormalitiesmentioning
confidence: 99%